(3GdEYdGe HSfJg Ydjg GdSdGes - (3oenZrdWGj Hf nbpdjL Hf YHO Gddg GdHcLQj GdeUQj GdMcQj GdMfaj, CHh YHO Gddg, YdGA GdOjf , J (B762 (3g` s; (3eMeO Hf jRjO GdQHYj GdbRhjfj, CHh YHO Gddg, GHf eGLI,J (B273 (3g` s
(3ChdgG (B:s
(3jHJOF HcJGH GdWgGQI s
(3BNQgG (B:s
(3hjfJgi HHGH GdhVhA ef eS GdPcQ s
(3ef fSNI KGfjIs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdMOjK h GdeUWdMs